2016
DOI: 10.1099/jmm.0.000233
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant presence of Aspergillus fumigatus and Stenotrophomonas maltophilia in the respiratory tract: a new risk for patients with liver disease?

Abstract: Concomitant lung colonization by Aspergillus fumigatus and Stenotrophomonas maltophilia was reported mainly in patients with cystic fibrosis (CF) and immunocompromised patients. The aim of the study was to assess the frequency of co-culture of A. fumigatus and S. maltophilia in respiratory samples of hospitalized patients, and to determine its associated factors. Between 2007 and 2011, all patients who had A. fumigatus in their respiratory samples were retrospectively enrolled in the study. Their clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…It should be noted that one of the frequent bacterial isolates was Stenotrophomonas sp. detected in "tempera samples" together with Aspergillus (probes 25, 27), suggesting a possible interaction between the two microorganisms, as previously shown for S. maltophilia and A. fumigatus [36]. A wide spectrum of enzymatic activity demonstrated by various Stenotrophomonas spp.…”
Section: Identification Of Microorganisms In Samples and Correspondinsupporting
confidence: 63%
See 1 more Smart Citation
“…It should be noted that one of the frequent bacterial isolates was Stenotrophomonas sp. detected in "tempera samples" together with Aspergillus (probes 25, 27), suggesting a possible interaction between the two microorganisms, as previously shown for S. maltophilia and A. fumigatus [36]. A wide spectrum of enzymatic activity demonstrated by various Stenotrophomonas spp.…”
Section: Identification Of Microorganisms In Samples and Correspondinsupporting
confidence: 63%
“…S. maltophilia isolates could utilize a wide variety of substrates [37], which is likely due to a broad spectrum of enzymatic activities detected in Stenotrophomonas spp., enabling the bacteria to metabolize different materials. S. maltophilia is pathogenic for humans, and in many clinical cases co-infection with S. maltophilia and A. fumigatus was observed [36]. Iron is required for S. maltophilia biofilm formation and virulence [26]; however, after 48 h inoculum 25G containing Stenotrophomonas and Aspergillus grew better on tempera paints with cinnabar, CuPc, or without any pigments than on those with Fe-containing ochre, which was due to dominant fungal growth (S11.…”
Section: Plos Onementioning
confidence: 99%
“…This result may be at odds with our previous observation [29]. Indeed, in seven patients with liver disease an association between co-infection by A. fumigatus and S. maltophilia has been observed [30]. However, in this previous work, we were not able to distinguish between S. maltophilia infection and colonisation, which made it difficult to reach conclusions on the specific role of the bacterium in the respiratory pathology.…”
Section: Discussioncontrasting
confidence: 89%
“…Several studies have reported A. fumigatus colonization in patients with chronic lung disease, especially chronic obstructive pulmonary disease (COPD) and CF, probably due to the lung structural changes and the heavy courses of antibiotics ( Bafadhel et al, 2014 ; Sabino et al, 2015 ). Stenotrophomonas maltophilia (Sm) is an emergent ubiquitous Gram-negative bacillus ( Chotirmall and McElvaney, 2014 ) whose antibiotic resistance and biofilm formation capacity promote opportunistic pathogenicity in CF or in immunocompromised patients ( Calza et al, 2003 ; Jacquier et al, 2011 ; Cabaret et al, 2016 ). Recently, S. maltophilia was positively associated with Aspergillus species infections in patients with CF suggesting that such co-infections are common and may alter therapeutic responses in these patients ( Granchelli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%